Analisis Faktor-faktor yang Mempengaruhi Mahasiswa Memanfaatkan Layanan Penelusuran - Indah Wijaya Antasari (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The information retrieval services is a service that interests university library users. There is a significant increase of students completing their thesis using searching services during the COVID-19 pandemic. This study aims to find factors in the utilization of research searching services. It is Using a quantitative approach with exploratory factor analysis (EFA). The study population was 376 students who submitted searching services during the pandemic (March-December 2020),using Slovin formula get a sample 82 respondents. The primary data source from the questionnaire. The results showed that only one (1) factor for the variable use of research searching services, with seven (7) statements: P1, P2, P3, P4, P5, P6, and P7, but, the P8 idea is not continued for analysis because the results of the commonalities test showed that the extraction value is less than 0.5. The conclusion is the factor variables that influence IAIN Purwokerto students to use the searching service have no dimension (there is only one factor) that is factors for completing thesis, indicators of these factors are seven statements: requires an example of a thesis; enriches material for a thesis; knows how to describe the background; looks for the right theory; gets an appropriate research method; knows how I should explain the discussion; and knows how to conclude the results of a research.